Taxonomic identification and antagonistic activity of Streptomyces luomodiensis sp. nov. against phytopathogenic fungi - Qi, Dengfeng; Liu, Qiao; Zou, Liangping; Zhang, Miaoyi; Li, Kai; Zhao, Yankun; Chen, Yufeng; Feng, Junting; Zhou, Dengbo; Wei, Yongzan; Wang, Wei; Zhang, Lu; et al. (Frontiers in Microbiology, 2024)
Banana wilt caused by Fusarium oxysporum f. sp. cubense tropical race 4 (Foc TR4) is a devastating fungal disease. Biocontrol strategies hold immense potential in inhibiting the spread of Foc TR4. Here, thirty actinobacteria were isolated from soils and screened for their antagonistic activity against Foc TR4. Strain SCA4-21 T was selected due to its strongest antagonistic activity against Foc TR4. Strain SCA4-21 T also exhibited strong antagonistic activity against other eight phytopathogenic fungi. The strain was identified as the genus Streptomyces according to the physiological, biochemical and phenotypic characteristics. The phylogenetic trees of 16S rRNA sequences demonstrated that strain SCA4-21 T formed a subclade with S. iranensis HM 35 T and/or S. rapamycinicus NRRL B-5491 T with low bootstrap values. Considering that 16S rRNAs did not provide a sufficient resolution for the species-level identification, the whole genome of strain SCA4-21 T was sequenced. Multi-locus sequence analysis (MLSA) based on five house-keeping gene alleles (atpD, gyrB, recA, rpoB, and trpB) revealed that strain SCA4-21 T clustered into S. hygroscopicus subsp. hygroscopicus NBRC 13472 T with 100% of bootstrap value. Analysis of the genome-based phylogeny approved also the results.Average nucleotide identity (ANI) and digital DNA-DNA hybridization (dDDH) were 91.26% and 44.30% values below the respective species level threshold of 95% and 70%. Hence, strain SCA 4-21 T represented a novel species within the genus Streptomyces, named as Streptomyces luomodiensis sp.nov. The type strain is SCA4-21 T (=GDMCC4.340 T = JCM36555 T ). By the CAZymes analysis, 348 carbohydrate-active enzymes (CAZymes) were detected, including 15 chitinases and 8 β-1,3glucanases. The fermentation broth of strain SCA4-21 T , exhibiting strong antagonistic activity against Foc TR4, demonstrated high activities of chitinase and β-1,3-glucanase which might be involved in antifungal activity. Our results showed an innovative potential biocontrol agent for managing plant fungal diseases, specifically banana fusarium wilt.